N-gram Smoothing on Expected Fractional Counts - Levit, Michael; Parthasarathy, Sarangarajan; Chang, Shawn (Microsoft Corporation, 2018)
This is a companion document to our Interspeech 2018 paper ``What to Expect from Expected Kneser-Ney Smoothing''. It provides additional details and considerations regarding derivation, optimizations and extensions of the n-gram smoothing on expected fractional counts, a technique originally introduced in Zhang et al 2014.